33.9k views
1 vote
Factoriser 1-9x²-y²-6xy​

2 Answers

4 votes

Answer:

(1 - 3x - y)(1 + 3x + y)

Explanation:

Given

1 - 9x² - y² - 6xy

= 1 - (9x² + y² + 6xy) ← perfect square

= 1 - (3x + y)²

1 - (3x + y)² is a difference of squares and factors in general as

a² - b² = (a - b)(a + b)

Here a = 1 and b = 3x + y, thus

1 - (3x + y)²

= (1 - 3x - y)(1 + 3x + y) ← in factored form

2 votes

Answer:

- (1+3x+y) (3x+y-1)

User Pius Lee
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.